2010
DOI: 10.1590/s1807-59322010001000006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between two shock wave regimens using frequencies of 60 and 90 impulses per minute for urinary stones

Abstract: PURPOSE:Two different regimens of SWL delivery for treating urinary stones were compared.METHODS:Patients with urinary stones were randomly divided into two groups, one of which received 3000 shocks at a rate of 60 impulses per minute and the other of which received 4000 shocks at 90 impulses per minute. Success was defined as stone‐free status or the detection of residual fragments of less than or equal to 3 mm three months after treatment. Partial fragmentation was considered to have occurred if a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…They found that slow delivery rate of SWL has beter stone clearance results than fast delivery rate [5]. Mazzucchi et al [35] found no signiicant diferences in the stone-free rate and complications development by reducing the total number of impulses from 4000 to 3000 and the frequency from 90 to 60 impulses/min. Vakalopoulos [36] developed a mathematical model to predict ESWL outcomes where predictive equations can be generated for diferent lithotripters.…”
Section: Recent Trends In Extracorporeal Shockwave Lithotripsy (Eswl)mentioning
confidence: 99%
“…They found that slow delivery rate of SWL has beter stone clearance results than fast delivery rate [5]. Mazzucchi et al [35] found no signiicant diferences in the stone-free rate and complications development by reducing the total number of impulses from 4000 to 3000 and the frequency from 90 to 60 impulses/min. Vakalopoulos [36] developed a mathematical model to predict ESWL outcomes where predictive equations can be generated for diferent lithotripters.…”
Section: Recent Trends In Extracorporeal Shockwave Lithotripsy (Eswl)mentioning
confidence: 99%
“…3 Currently, frequencies from 60-90 shocks/minute have been chosen, with a gradual increase in energy with the aim of increasing the fragmentation of the stone and reducing the morbidity of the procedure. 4,5 A recent meta-analysis proved the superior efficacy of ESWL with a frequency of 60 in relation to 120 shocks per minute. 4 And as demonstrated by Pace et al, 6 this benefit is clearest in calculi over 10 mm.…”
Section: Technical Principlesmentioning
confidence: 99%
“…[68]. Mazzucchi et al found no significant differences in the stone-free and complication rates were observed by reducing the total number of impulses from 4000 to 3000 and the frequency from 90 to 60 impulses per minute [69] . Chacko et al favors a frequency reduction, arguing that 90 sw/min treatment gave better results in terms of stone fragmentation compared to 120 sw/min [70].…”
Section: Reviewmentioning
confidence: 99%